Pengembangan Media Pembelajaran Berbasis Video Tutorial untuk Mengenal Mikroba yang Digunakan dalam Pembuatan Tempe pada Matakuliah Mikrobiologi - Lailia Nabila Larasati (Multiverse: Open Multidisciplinary Journal, 2023)
The obstacles that occur in microbiology learning are in the facilities because the microbiology course requires a laboratory to carry out practicums but as a result of online access to the laboratory being closed so students can only understand through material only so that only practicum guidebooks as learning media in carrying out practicum activity steps result in students not understanding. Particularly in food microbiology material, many students failed to carry out practicums in making food, one of which was in making tempe. Tempe has certain critical points in the success of its products so students must understand techniques to overcome these critical points in order to reduce failures, this can be done when we do practicum. This research will be conducted at Medan State University. The development model applied in this research is 4D. The 4D models include define, design, develop, and disseminate. The data collection technique used was a questionnaire for experts and students. The experts consist of material experts and media experts, while for students of the Stambuk 2020 biology education study program. The results of this study show that video tutorial-based learning media for food microbiology is feasible and effective, and has increased by 37.7%. The implications of this learning video are expected to help lecturers in learning microbiology.